Labraunda’nın Yeni Bilmecesi: Su Kompleksi Kazıları 2013-2015 Kazı Sezonu Değerlendirmesi / The Mistery of Labraunda: Water Complex Excavations between 2013-2015 - Çakmaklı, Ömür Dünya (Journal of History Culture and Art Research, 2016)
The Mistery of Labraunda: Water Complex Excavations Abstract: Zeus Labraundos Sacred Site, which is located 13 km to the northeast of Milas, and which is one of the most majestic and most protected sites in the Karia Region, is in a key position to illuminate the history of Karia. The ongoing excavations revealed very important scientific information concerning the details of this history. Moreover, the "water" springs of the Karia Region, and mainly the Milas Region and Inner Karia that also include Labraunda, that are still important today; and the structures related to these springs that bestow a privileged importance to this region still didn't completely receive the attention they deserve. The "Water Complex" structure, which was discovered unexpectedly during the rearrangement works focused around Temenos will be very useful to resolve the water system mechanism developed in Labraunda, which takes its holy properties from water. This paper shares information obtained from archeologic excavations between 2013-2015. Labraunda’nin Yeni Bilmecesi: Su Kompleksi Kazıları 2013-2015 Kazı Sezonu Değerlendirmesi Öz Milas’ın 13 km. kuzeydoğusunda yer alan ve Karia Bölgesinin en görkemli, en iyi korunmuş alanlarından olan Zeus Labraundos Kutsal alanı, Karia tarihini aydınlatmada anahtar konumdadır. Halen devam eden kazı çalışmaları, alana ait bu tarihin detaylandırılmasına ilişkin oldukça önemli bilimsel verileri günümüze ulaştırmıştır. Bununla birlikte alana ayrıcalıklı bir önem kazandıran; Karia Bölgesinin ve esas olarak Labraunda’nın içinde yer aldığı Milas Bölgesi ve İç Karia’nın günümüzde dahi önemini koruyan “su” kaynakları ve bu kaynaklarla ilintili yapıları henüz hak ettiği odağa tam olarak kavuşamamıştır. 2013 yılında, temenosun çevresinde yoğunlaşan düzenleme çalışmaları esnasında beklenmedik bir şekilde tespit edilen “Su Kompleksi” yapısı, kutsallık özelliğini su’dan alan Labraunda’da geliştirilen su sistemi mekanizmasını çözümlemede oldukça faydalı olacaktır. Bu makalede 2013-2015 kazı sezonunda elde edilen bilgi ve bulgular paylaşılmıştır.